2005
DOI: 10.1038/nbt1081
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent stimulation of the mammalian innate immune response by synthetic siRNA

Abstract: Short interfering RNAs (siRNAs) that mediate specific gene silencing through RNA interference (RNAi) are widely used to study gene function and are also being developed for therapeutic applications. Many nucleic acids, including double- (dsRNA) and single-stranded RNA (ssRNA), can stimulate innate cytokine responses in mammals. Despite this, few studies have questioned whether siRNA may have a similar effect on the immune system. This could significantly influence the in vivo application of siRNA owing to off-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
922
5
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,100 publications
(957 citation statements)
references
References 29 publications
23
922
5
7
Order By: Relevance
“…The observed effects were cell type dependent, thus suggesting the involvement of cellular factors that are differentially expressed by mammalian cells. In this respect, we [19] and others [20,21] have recently demonstrated that PKR and TLR3 do not represent the major mechanisms by which chemically synthesized siRNA activate innate immunity. Moreover, we found that single-stranded (ss) siRNA (sense or antisense strands) and ds siRNA separately could activate innate immunity genes.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The observed effects were cell type dependent, thus suggesting the involvement of cellular factors that are differentially expressed by mammalian cells. In this respect, we [19] and others [20,21] have recently demonstrated that PKR and TLR3 do not represent the major mechanisms by which chemically synthesized siRNA activate innate immunity. Moreover, we found that single-stranded (ss) siRNA (sense or antisense strands) and ds siRNA separately could activate innate immunity genes.…”
Section: Introductionmentioning
confidence: 82%
“…In both cases, internalization of RNA and endosomal maturation is required for immune stimulation, suggesting the involvement of endosomal TLR, in particular TLR7 and TLR8. Indeed, inhibitors of endosomal maturation, such as bafilomycin, abrogated immune activation [19,21]. The data reported by Hornung et al [20] and Judge et al [21] suggest that immunostimulatory motifs are equally recognized within the context of either ss siRNA or siRNA duplexes because the magnitude of cytokines and IFN responses was comparable for both molecules.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cela a déjà été observé dans les organes périphériques, mais reste peu présent dans le système nerveux central du fait de la protection du cerveau par la barrière hémato-encéphalique [36]. Cependant, une quantité anormale de matériel génétique dans le cerveau peut conduire à l'expression par les neurones de protéines reconnues par le système immunitaire, et donc à une destruction des cellules traitées par l'organisme [37].…”
Section: Revuesunclassified
“…[7][8][9][10] Morrissey et al 4 investigated whether or not SNALP delivered, nonbackbone-modified siRNAs were immunostimulatory, and sure enough they were. The fact that the unmodified siRNAs were immunostimulatory indicates that they are subject to endosomal trafficking, where the RNA-activated Toll-like receptors 3 and 7 reside.…”
Section: News and Commentarymentioning
confidence: 99%